PENGARUH PERILAKU MEROKOK ORANG TUA TERHADAP STATUS GIZI (UNDERWEIGHT) ANAK USIA 5 - 12 TAHUN : ANALISIS DATA SEKUNDER RISKESDAS 2018 - Bunga Ellen Engelina, (2022)
Malnutrition can interfere with the growth and development of children, and can increase the risk of disease. This study aims to determine the relationship between parental smoking behavior and the nutritional status of children aged 5-12 years in Indonesia. Basic Health Research (RISKEDAS) 2018 was conducted using a quantitative approach with a cross-sectional study, namely the type of research carried out by observing independent variable data and only one time design with the aim of knowing the relationship between one variable and another. The bivariate test with chi square showed that there was no significant relationship between parental smoking behavior and the incidence of underweight, which was indicated by the results of bivariate analysis (p value = 0.851 > 0,05). And the results of the multivariate test with logistic regression showed that there was no influence between parental smoking behavior on the incidence of underweight, this was indicated (p value = 0.851 > 0,25), which means there was no effect between the two. Prevention of underweight in children can be done in various ways. One of them is to avoid various factors that can trigger underweight status, such as place of residence, gender, age, parental education, parental occupation, and parental smoking behavior. In children, this preventive step can be done early by parents.